Acid Sensing Ion Channels (ASICs) in NS20Y cells – potential role in neuronal differentiation. Issue 1 (December 2016) - O'Bryant, Zaven; Leng, Tiandong; Liu, Mingli; Inoue, Koichi; Vann, Kiara; Xiong, Zhi-gang
Abstract Cultured neuronal cell lines can express properties of mature neurons if properly differentiated. Although the precise mechanisms underlying neuronal differentiation are not fully understood, the expression and activation of ion channels, particularly those of Ca2+ -permeable channels, have been suggested to play a role. In this study, we explored the presence and characterized the properties of acid-sensing ion channels (ASICs) in NS20Y cells, a neuronal cell line previously used for the study of neuronal differentiation. In addition, the potential role of ASICs in cell differentiation was explored. Reverse Transcription Polymerase Chain Reaction and Western blot revealed the presence of ASIC1 subunits in these cells. Fast drops of extracellular pH activated transient inward currents which were blocked, in a dose dependent manner, by amiloride, a non-selective ASIC blocker, and by Psalmotoxin-1 (PcTX1), a specific inhibitor for homomeric ASIC1a and heteromeric ASIC1a/2b channels. Incubation of cells with PcTX1 significantly reduced the differentiation of NS20Y cells induced by cpt-cAMP, as evidenced by decreased neurite length, dendritic complexity, decreased expression of functional voltage gated Na+ channels. Consistent with ASIC1a inhibition, ASIC1a knockdown with small interference RNA significantly attenuates cpt-cAMP-induced increase of neurite outgrowth. In summary, we described the presence of functional ASICs in NS20Y cells and demonstrate that ASIC1a plays a role in the differentiation of these cells.